2009
DOI: 10.9795/bullgsj.59.327
|View full text |Cite
|
Sign up to set email alerts
|

Paleaogeography and Climatic Change recorded on Viviparidae Carbon and Oxygen Isotope in Mae Moh Coal Mine, Northern Thailand

Abstract: Viviparidae fossil collected from the R-, Q-, and K-coal zones of the Mae Moh coal mine, northern Thailand were analyzed for 13 Carbon and 18 Oxygen isotopes at Akita University, Japan. The result reveals that Viviparidae of the lower part of the coal mine contribute much heavier carbon isotopes than the upper part. The results revealed that Viviparidae shell O ‰ value between -6.64 to -7.04 ‰ PDB. The isotopic results of Viviparidae fossil shells from Mae Moh basin show the gradually change from the R-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Thus, reduced dispersal from India to Asia could be explained by decelerated phylogenetic diversification during the establishment of more seasonal conditions in the source biota. The same applies for the interval from 24 to 21 Ma, when MDE to the Indian subcontinent from Asia was stagnant, as there is good evidence that the climate in northern mainland SE Asia was warm temperate during the Oligocene and Early Miocene 21 29 30 , changing again to more perhumid climates only during the Middle Miocene 30 .…”
Section: Resultsmentioning
confidence: 87%
“…Thus, reduced dispersal from India to Asia could be explained by decelerated phylogenetic diversification during the establishment of more seasonal conditions in the source biota. The same applies for the interval from 24 to 21 Ma, when MDE to the Indian subcontinent from Asia was stagnant, as there is good evidence that the climate in northern mainland SE Asia was warm temperate during the Oligocene and Early Miocene 21 29 30 , changing again to more perhumid climates only during the Middle Miocene 30 .…”
Section: Resultsmentioning
confidence: 87%
“…This structural trap consists of fine-particle claystone (NK) acting as a seal that covers the prospective storage formation of limestone (TR 4 ) located underneath. Further lithology details in the Mae Moh basin can be found in the work by Ratanasthien et al…”
Section: Co2 Storage Formation and Experimental Methodsmentioning
confidence: 99%
“…44 More scores were even added to top-rank this source−sink pair due to the short distance between them (∼15 km) and hence considerably low CO 2 transportation cost from the source (power plant) to the coal mine sink area. A specific location (cross section line N30.5) with promising formation (i.e., structural trap and sedimentary basins) was selected in the current study by reviewing updated information, 45,46 where the rock samples were cored for examinations (Figure 2b). This structural trap consists of fine-particle claystone (NK) acting as a seal that covers the prospective storage formation of limestone (TR 4 ) located underneath.…”
Section: Co 2 Storage Formation and Experimental Methodsmentioning
confidence: 99%
“…Thus, rocks deposited in these environments range from fluvial sandstones with associated finer-grained overbank deposits to lacustrine mudstones and oil shales, and to mire-associated claystones and lignitic coal seams (Morley and Racey, 2011;Friederich et al, 2016). Considering that many of the basins in Thailand are both sources of coal and hydrocarbons and paleontologically important, significant data exists on intra-basin stratigraphy, biostratigraphy, magnetostratigraphy, and plant-and animalbased paleoecology (Benammi et al, 2002(Benammi et al, , 2010Ratanasthien, 2002;Songtham et al, 2005;Ratanasthien et al, 2008;Thasod et al, 2008;Coster et al, 2010;Sepulchre et al, 2010;Friederich et al, 2016;Grohé et al, 2020;among others). This makes it possible to organize individual coal seams that occur within the basins by age.…”
Section: Thailand Stratigraphymentioning
confidence: 99%
“…Plant-based reconstructions from coal basins in northern Thailand have indicated a transition from warm-temperate climates in the early Burgidalian (Chiang Mai lignites) to tropical climates by the late Burgidalian-early Langhian (Hod lignites) that largely persisted through the early middle and upper middle Miocene (Ratanasthien et al, 2008;Morley and Racey, 2011). It has been suggested that these changes coincide with increasing paleotopographic relief and intensification of the SE Asian monsoon (Morley, 2012;Steinthorsdottir et al, 2021).…”
Section: Paleoclimatementioning
confidence: 99%